New functional training for sports - Boyle, Michael, ....- (Champaign : Human Kinetics, 2016)
Michael Boyle, one of the world's leading sport performance coaches, presents the concepts, methods, exercises and programmes that maximise athletes' movements in competition. Self-reinforcing progressions in exercises for the lower body, core, upper body, and ultimately total body give athletes the balance, proprioception, stability, strength and power they require for excelling in their sports. Sample programmes assist in the customisation process and ensure each aspect of preparation for physical performance. New Functional Training for Sports goes beyond traditional exercise descriptions and explanations, incorporating full-colour, high-definition composites of foundational movements as well as online access to video demonstrations, commentary and analysis of key exercises.
Includes exclusive acceess to online video library
Keywords: Krachttraining